Go east: On the impact of the Transiberian Railway on economic development in Eastern Russia - Sebastian Seiffert (Universität Hohenheim, Fakultät Wirtschafts- und Sozialwissenschaften, 2019)
This paper addresses the question whether or not large-scale infrastructure investments have a causal effect of local economic development. By using a novel instrumental variable approach based on historical trade and travel routes across the Russian East, I am able to identify a causal and negative effect of remoteness to the Transsiberian Railway on local economic activity as measured by nocturnal lights emission.
urn:nbn:de:bsz:100-opus-16063
Keywords: O11; O18; R11; R40; 330; Transport Costs; Railway; Russia; Nightlights; Regional Economics; Development